Sistem Pakar Untuk Menyusun Formula, Kandungan Gizi, dan Harga Pakan Ikan - Suwarsito Suwarsito; Hindayati Mustafidah (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2014)
Development of expert system has been widely applied to various fields of study, including education (for tutorial), academics, medicine (to diagnose the disease either man or animal), and so on. In this study applied expert system to compile a formula feeding fish include nutrient and estimated price of the feed raw material. The system was built using backward chaining using Turbo C++ programming language. This system is interactive. User should answer the system’s question of type and age of the fish, as well as a range of feed raw materials around, the user will get the required nutrient content information as well as advice on solutions in the form of formula feed and how much raw material feed is needed as well as the estimated price